Comparison of effects of Bupivacaine and Ropivacaine in patients undergoing elective Caesarean section - Subba, Sangeeta; Arjun Chhetri, Arjun; Bhattarai, Rupak (Birat Journal of Health Sciences, 2020)
Introduction: Spinal anesthesia is considered a reasonable choice for cesarean section. Bupivacaine and ropivacaine have been used as intrathecal drugs alone or in combination with various opioids. Ropivacaine is considered a valid and safe alternative to bupivacaine for spinal anesthesia. Objectives: To compare the efficacy and safety of hyperbaric ropivacaine with hyperbaric bupivacaine in spinal anesthesia for elective cesarean section. Methodology: Sixty pregnant women undergoing elective cesarean section were allocated into two groups. Group R received 3 ml of 0.5% hyperbaric ropivacaine (2 ml 0.75% plain ropivacaine mixed with 1 ml of 25 %dextrose) and Group B received 2.5 ml of 0.5% hyperbaric bupivacaine. Both the groups were compared in terms of onset of sensory and motor block, regression of sensory and motor block, duration of analgesia and side effects. Results: The onset of sensory block was comparable in both groups but was statistically insignificant. The onset of motor block in Bupivacaine(7.53 ± 1.72) min was faster when compared to Ropivacaine group(14.33 ± 6.19) min. Regression of sensory and motor block both were faster in Ropivacaine group. Duration of analgesia was longer in Bupivacaine group(131.17 ± 32.95)min than Ropivacaine group(125.33 ± 30.54)min. Conclusion: Ropivacaine can be used as an alternative to Bupivacaine for spinal anesthesia in cesarean section but has a shorter duration of sensory and motor block.